Perception on reliability and responsiveness of Polis DiRaja Malaysia (PDRM): a study among citizens in Putrajaya / Mohd Syafiq Mat Saruji, Yarina Ahmad and Azizan Zainuddin - Mat Saruji, Mohd Syafiq; Ahmad, Yarina; Zainuddin, Azizan (Faculty of Administrative Science & Policy Studies (FASPS), Universiti Teknologi MARA (UiTM) Shah Alam, 2018)
This paper presents the perception of Putrajaya citizens on reliability and responsiveness of the services provided by Polis DiRaja Malaysia (PDRM). The main objectives of this study are: (i) to determine the level of reliability and responsiveness of police; (ii) to examine the influence of independent variables (accessibility, competency, manners and fairness) on the dependent variables (reliability and responsiveness); (iii) to scrutinize the main factor that influence reliability and responsiveness of the services; and (iv) to examine the influence of gender as a moderating effect on the relationship between both independent and dependent variables. A quantitative approach of using self-administered questionnaires was applied in this study. A total number of 146 Putrajaya citizens responded to the survey based on simple random sampling technique. The findings of this study revealed that the level of reliability and responsiveness of police service were moderate (Mean=3.744, Std. Dev. 0.736; Mean=3.703, Std. Dev. 0.705). Furthermore, competency and manners were found to have significant influence on reliability (p<0.00, p=0.00); and the main factor that influenced reliability was manners (p=0.00, β=0.42). In terms of responsiveness, competency and manners were also found to have significant influence (p<0.00, p=0.00), with competency being the main factor that influence responsiveness (p=0.00, β=0.43). Notably, gender was found to have no moderating effect on the relationship between both independent and dependent variables (p>0.05). The study concludes that Putrajaya citizens perceived the reliability and responsiveness of police service to be at a moderate level (between average and good), where manners was found to be the main factor influencing the reliability of police services, and competency was recognized as the most influential factor to enhance the responsiveness of police services. This study serves as an indicator for improvement in the police services - in line with PDRM’s mission: “To provide professional and quality services in protecting the country to ensure public safety, security and prosperity”.